Using Digital Technology to empower users with special needs at the University of Guyana Library. - Harris, Clyden; LaRose, Simmone; Lowe, Debra (Advances in Social Sciences Research Journal, 2020)
The purpose of this research is to highlight the digital technology programmes and activities implemented by the Library professionals at the University of Guyana Library, to empower users with special needs. The use of digital technology in libraries is redefining the way information is disseminated and it has influenced the roles of all information professionals. As digital technology evolved, Librarians have been forced to revolutionise their way of operating and employ a variety of ways to adjust; not only to their changing roles but also to find ways to enhance high quality service delivery. These innovations not only brought changes to the delivery services but also served to propel inclusivity for previously marginalised groups, including persons with special learning needs, who are physically challenged, have cognitive challenges, experiencing varying levels of competencies or other socio-economic difficulties. The final benefits being envisioned would be lifelong learning and success in all aspects of student's lives. Iin this era of digital transformation, University Libraries must therefore combine technology and human interaction in all of its services for access by all to accomplish this vision. Recognising that there was a practice to generalise the user population, even though their learning capabilities differed, Librarians at the University of Guyana Libraries (Turkeyen and Tain) sought to devise ways in which all users would benefit from all of the services offered using digital technology. Through this medium, students with special needs /differently-abled who were often marginalised due to different learning capabilities are now able to have an equal opportunity to access research content with ease. Librarians at the University of Guyana Library have illustrated how the use of digital technology at its academic library has helped to promote scholarship and encourage high quality research by providing online services with remote access and links to external resources. This paper expands on the digital programmes that the University of Guyana Libraries provides for students with special needs and the measures taken to empower special needs users through digital technologies.